2020
DOI: 10.1088/1748-0221/15/03/c03033
|View full text |Cite
|
Sign up to set email alerts
|

First calorimetric energy reconstruction of beam events with ARAPUCA light detector in protoDUNE-SP

Abstract: First calorimetric energy reconstruction of beam events with ARAPUCA light detector in protoDUNE-SP D.Totani, a,b F. Cavanna, b on behalf of DUNE collaboration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Most of the nonlinearity was then removed. The intercept of the linear fit after correction indicates an energy offset of -56 ± 14 MeV, in better agreement with the expected beam electron energy loss in the materials before entering the TPC -details of this study can be found in [67]. Based on the linearity of the light response, the relative calorimetric energy resolution 𝜎 𝐸 /𝐸 e is obtained from the 𝜎 𝑁 /𝑁 Ph ratio of the light response (figure 70 -right).…”
Section: Beam Electrons and Em Showerssupporting
confidence: 78%
See 1 more Smart Citation
“…Most of the nonlinearity was then removed. The intercept of the linear fit after correction indicates an energy offset of -56 ± 14 MeV, in better agreement with the expected beam electron energy loss in the materials before entering the TPC -details of this study can be found in [67]. Based on the linearity of the light response, the relative calorimetric energy resolution 𝜎 𝐸 /𝐸 e is obtained from the 𝜎 𝑁 /𝑁 Ph ratio of the light response (figure 70 -right).…”
Section: Beam Electrons and Em Showerssupporting
confidence: 78%
“…Since the energy loss occurs downstream of the momentum spectrometer, this energy degradation and its fluctuation do not appear in the incident beam energy spectra and it is evaluated by simulations (∼ 2%). Other contributions to the resolution, such as non-uniformity on the detector illumination, channel to channel response variation and possible shower leakage across the cathode, have been investigated and shown to be negligible [67]. The light yield and resolution response obtained from a single ARAPUCA module is adequate.…”
Section: Jinst 15 P12004mentioning
confidence: 99%
“…On the other hand, charge-selective contact devices [6] follow a three-layer structure, including a thin layer of metal oxides where hole mobility exceeds electron mobility (MoO 𝑥 or WO), a thick layer of intrinsic a-Si:H, and a thin layer of a metal oxide where electron mobility is greater than hole mobility (such as TiO 2 or Aluminum-doped Zinc Oxide).…”
Section: Jinst 19 C04025 2 Sensors and Setup Descriptionmentioning
confidence: 99%
“…The Deep Underground Neutrino Experiment (DUNE) promises one of the largest highly instrumented fiducial detector masses of any future large underground facility [461,462]. With 40 kt of liquid argon (LAr) some 1500 m below Lead, South Dakota to shield against cosmic ray backgrounds, DUNE's immense wire readout particle ionization charge-collection system across four separate modules forms its three-dimensional LAr time projection chambers, allowing scientists to exploit bubble-chamber quality images [463][464][465] for world-leading precision physics studies of the SM and beyond. With potentially MeV-scale precision [466], the ability to distinguish γ and e species [467], low cosmic µ backgrounds, and very low LAr ionization kinetic energy thresholds for even heavy charged species such as protons (ps) [57,462], the overall physics potential of DUNE goes far beyond its initial purpose as a ν detector built to better constrain and measure oscillation parameters such as δ CP .…”
Section: Dunementioning
confidence: 99%